A graphite composite material and preparation method thereof

By forming a Cr flat layer and a CrN oxidation-resistant layer on the surface of the graphite matrix, the problems of oxidation corrosion and surface impermanence in high-temperature aerobic environment are solved, and its oxidation resistance and application fields are improved.

CN115896701BActive Publication Date: 2025-04-08BIEL OPTIC HUIZHOU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211612104.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-04-08
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

Graphite materials are prone to oxidation and corrosion in high-temperature aerobic environment, and their layered structure leads to soft and wear-resistant surfaces, limiting the expansion of their application fields.

Method used

By attaching a flat layer formed by metal Cr and an oxidation-resistant layer formed by metal compound CrN on the surface of the graphite matrix, the antioxidation-resistant layer is ensured to be stable under high temperature conditions and improve the antioxidation ability of the graphite material.

Benefits of technology

It has achieved good and stable antioxidant properties of graphite materials in high-temperature aerobic environment, and expanded its application areas, including machinery, electronics, semiconductors, metallurgy and bioengineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896701B_ABST
    Figure CN115896701B_ABST
Patent Text Reader

Abstract

A graphite composite material and a preparation method thereof. The graphite composite material comprises a graphite substrate, a flat layer attached to the surface of the graphite substrate, and an anti-oxidation layer attached to the surface of the flat layer. The preparation method comprises the following steps: step S1, cleaning the graphite substrate; step S2, forming a flat layer on the surface of the graphite substrate; step S3, forming an anti-oxidation layer on the surface of the flat layer. The anti-oxidation layer of the graphite composite material can be strongly and stably attached to the surface of the graphite substrate through the flat layer in a high-temperature aerobic environment, so that the anti-oxidation layer will not fall off in a high-temperature aerobic environment, which is conducive to improving the stability and reliability of the anti-oxidation ability of the graphite material in a high-temperature aerobic environment, and can greatly broaden the application field of the graphite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite materials, in particular to a surface modification technology of graphite materials, and more particularly to a graphite composite material and a preparation method thereof. Background Art

[0002] Graphite materials have excellent electrical conductivity, high temperature resistance, thermal conductivity and self-lubricating properties, a small thermal expansion coefficient, excellent thermal shock resistance, and are easy to machine. Therefore, they are widely used in the fields of machinery, electronics, semiconductors, metallurgy, bioengineering, etc., and have become an indispensable special engineering material; however, graphite materials have poor high-temperature oxidation resistance, and will undergo oxidative corrosion in high temperature and oxygen environments, which will cause gradual damage to components; in addition, the special layered SP 2 The structure makes its surface soft and not wear-resistant, and a slight scratch can cause the graphite surface to fall off; to a certain extent, it limits the expansion of the application field of graphite materials.

[0003] In order to overcome the above problems, the method commonly used in the industry is to use surface coating technology to prepare a suitable anti-oxidation film on the surface of the graphite material to protect the graphite material and prevent the graphite material from undergoing oxidation reaction with oxygen in a high-temperature aerobic environment and causing loss of the matrix. At the same time, it can also prevent the surface graphite powder from falling off due to human contact operations.

[0004] However, due to the special layered SP of graphite materials 2 The structure and its low thermal expansion coefficient have led to the high temperature oxidation resistant coatings (e.g., NbC coatings, ZrC coatings, CNSiCr coatings, SiC / SiO 2 Coating, Cr 2 C 3 coating, TiAlN coating), cannot adhere well to the surface of graphite material in high temperature oxygen environment, thus affecting the anti-oxidation performance of the coating.

[0005] In view of the above defects, it is necessary to develop a new type of graphite composite material and a preparation method thereof to overcome the above defects. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a graphite composite material and a preparation method thereof. The graphite material includes a graphite matrix and an anti-oxidation layer. The anti-oxidation layer can be stably attached to the surface of the graphite matrix in a high-temperature aerobic environment, so that the anti-oxidation layer will not fall off in a high-temperature aerobic environment. This is beneficial to improving the stability and reliability of the anti-oxidation ability of the graphite material in a high-temperature aerobic environment, and can greatly broaden the application field of the graphite material.

[0007] In order to solve the above technical problems, the technical solution adopted by the invention is to provide a graphite composite material including a graphite substrate, a flat layer attached to the surface of the graphite substrate, and an anti-oxidation layer attached to the surface of the transition layer. By sequentially attaching the flat layer and the anti-oxidation layer to the surface of the graphite substrate, due to the presence of the flat layer, the anti-oxidation layer can be strongly and stably combined with the graphite substrate through the flat layer even under high temperature conditions, so that the graphite composite material has good and stable anti-oxidation ability in a high-temperature aerobic environment, and further the graphite composite material can be widely used in the fields of machinery, electronics, semiconductors, metallurgy, bioengineering, etc.

[0008] In the graphite composite material provided by the present invention, the flat layer has a thickness of 50nm-900nm and is formed of metal Cr.

[0009] In the graphite composite material provided by the present invention, the thickness of the anti-oxidation layer is between 700nm and 8000nm and is formed by the metal compound CrN.

[0010] In the graphite composite material provided by the present invention, in the anti-oxidation layer, the atomic percentages of Cr and N are 50-80% and 20-50% respectively.

[0011] In order to solve the above technical problems, the present invention also provides a method for preparing the above-mentioned graphite composite material, and the preparation method comprises the following steps: step S1, cleaning the graphite substrate; step S2, forming a flat layer on the surface of the graphite substrate; step S3, forming an anti-oxidation layer on the surface of the flat layer.

[0012] In the preparation method provided by the present invention, the step S1 comprises: step S11, pre-cleaning: wiping the surface of the graphite substrate to be coated with alcohol; step S12, placing the sample: clamping the graphite substrate cleaned with alcohol on the hanging rod of the circular rotating rack in the magnetron multi-arc ion sputtering coating equipment, setting the circular rotating rack to revolve as a whole while the hanging rod rotates; step S13, glow cleaning: at a temperature of 170°C to 400°C and a vacuum degree of 3×10 -3 ~6×10 -3 The graphite substrate was glow plasma cleaned under the condition of Pa.

[0013] In the preparation method provided by the present invention, in the step S2, a two-stage arc coating method is used to form the flat layer on the surface of the graphite substrate; wherein, in the first stage, the Cr target arc current is set to 80A-120A, the duty cycle is 30%-80%, and the negative bias voltage is 450V-800V; and in the second stage, the Ti target arc current is set to 80A-120A, the duty cycle is 30%-80%, and the negative bias voltage is 80V-450V.

[0014] In the preparation method provided by the present invention, in the step S2, the duration of the first stage is shorter than the duration of the second stage.

[0015] In the preparation method provided by the present invention, in step S3, the argon gas flow rate is controlled to be 50sccm~700sccm, nitrogen is set as the reaction gas, the Cr target current is set to be 10A~40A, the negative bias voltage is 50V~200V, the duty cycle is 30%~80%, and the deposition time is 20min~120min.

[0016] In the preparation method provided by the present invention, in the step S3, the flow rate of nitrogen as a reaction gas is 50 sccm to 700 sccm.

[0017] The graphite composite material of the present invention can achieve at least the following beneficial effects:

[0018] 1. A flat layer composed of metal Cr is formed on the surface of the graphite substrate, which can appropriately reduce the unevenness of the graphite substrate surface. At the same time, the flat layer is prepared by arc coating technology, which has high energy, and the metal Cr on the lower surface of the flat layer can form a Cr-C chemical bond with the upper surface of the graphite substrate. In addition, the thermal expansion coefficient of Cr is small and similar to that of graphite. The stress difference between the Cr flat layer and the graphite substrate is small, and the Cr flat layer can be well combined with the graphite substrate. In addition, the Cr flat layer will not produce bad interface stress with the CrN anti-oxidation layer, and can provide a good growth substrate for the CrN anti-oxidation layer to be plated next, which is conducive to the formation of a dense CrN anti-oxidation layer coating on the surface of the graphite substrate. In short, the Cr flat layer can well connect the graphite substrate and the CrN anti-oxidation layer coating.

[0019] 2. Compared with the hard anti-oxidation layer commonly used in the prior art (for example, TiN, which is currently the most widely used in industrial applications), the CrN anti-oxidation layer has the advantages of lower internal stress, smaller thermal expansion coefficient, high hardness, good thermal stability, toughness, wear resistance, corrosion resistance and oxidation resistance. The CrN anti-oxidation layer can form a good, stable and long-term protection for the graphite matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings in the following description are only embodiments of the invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without creative work:

[0021] Figure 1 This is a schematic diagram of the membrane structure of the graphite composite material provided by the present invention. DETAILED DESCRIPTION

[0022] In order to facilitate understanding of the invention, the invention will be described more fully below with reference to the relevant drawings. Typical embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the invention more thorough and comprehensive.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The terms used in the specification of the invention herein are only for the purpose of describing specific embodiments and are not intended to limit the invention.

[0024] The present invention provides a graphite composite material, see Figure 1 , Figure 1 The schematic diagram of the film structure of the graphite composite material provided by the present invention is as follows: Figure 1 As shown, the graphite composite material includes a graphite matrix, a flat layer attached to the surface of the graphite matrix, and an anti-oxidation layer attached to the surface of the flat layer.

[0025] Specifically, the thickness of the planar layer is between 50nm and 900nm and is formed of metal Cr. For example, the thickness of the planar layer can be selected to be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, etc.

[0026] Specifically, the anti-oxidation layer is formed of a metal compound CrN with a thickness between 700nm and 8000nm. For example, the thickness of the anti-oxidation layer can be selected to be 700nm, 1000nm, 1500nm, 2000nm, 3000nm, 4000nm, 5000nm, 6000nm, 7000nm, 8000nm, etc. In the anti-oxidation layer, the atomic percentages of Cr and N are 50-80% and 20-50%, respectively. For example, in the anti-oxidation layer, the atomic percentages of Cr and N are 50%, 50%, or 60%, 40%, or 70%, 30%, or 80%, 20%, etc.

[0027] In the graphite composite material provided by the present invention, by sequentially attaching a flat layer and an anti-oxidation layer on the surface of a graphite substrate, the graphite composite material has good and stable anti-oxidation ability in a high-temperature oxygen environment, thereby making it widely used in the fields of machinery, electronics, semiconductors, metallurgy, bioengineering, etc. The specific reasons are as follows:

[0028] First, a flat layer composed of metal Cr is formed on the surface of the graphite substrate, which can appropriately reduce the unevenness of the surface of the graphite substrate. At the same time, the flat layer is prepared by arc coating technology, which has high energy, and the metal Cr on the lower surface of the flat layer can form a Cr-C chemical bond with the upper surface of the graphite substrate. In addition, the thermal expansion coefficient of Cr is small and similar to that of graphite. The stress difference between the Cr flat layer and the graphite substrate is small, and the Cr flat layer can be well combined with the graphite substrate. In addition, the Cr flat layer will not produce bad interface stress with the CrN anti-oxidation layer, and can provide a good growth substrate for the CrN anti-oxidation layer that needs to be plated next, which is conducive to the formation of a dense CrN anti-oxidation layer coating on the surface of the graphite substrate. In short, the Cr flat layer can well connect the graphite substrate and the CrN anti-oxidation layer coating.

[0029] In addition, compared with the hard anti-oxidation layer commonly used in the prior art (for example, TiN, which is currently the most widely used in industrial applications), the CrN anti-oxidation layer has the advantages of lower internal stress, smaller thermal expansion coefficient, high hardness, good thermal stability, toughness, wear resistance, corrosion resistance and oxidation resistance. The CrN anti-oxidation layer can provide good, stable and long-term protection for the graphite matrix.

[0030] The present invention also provides a method for preparing the graphite composite material as described above, the preparation method comprising the following steps:

[0031] Step S1, cleaning the graphite substrate. Specifically, it includes three stages: pre-cleaning, sample placement and glow cleaning.

[0032] Step S11, pre-cleaning: wiping the surface of the graphite substrate to be coated with alcohol;

[0033] Step S12, placing the sample: clamping the graphite substrate cleaned with alcohol on the hanging rod of the circular rotating frame in the magnetron multi-arc ion sputtering coating equipment and closing the hatch, setting the circular rotating frame to revolve as a whole while the hanging rod rotates to ensure the uniformity of the heated and subsequently sputtered deposited thin film. Preferably, the rotation frequency of the circular rotating frame in the magnetron multi-arc ion sputtering coating equipment is 25Hz to 50Hz;

[0034] Step S13, glow cleaning: furnace temperature 170℃~250℃, and vacuum degree 3×10 -3 ~6×10 -3After 1000 Pa, the graphite substrate is glow plasma cleaned. The cleaning time is preferably 10 min to 60 min. High-purity argon is used as the sputtering gas. The gas flow rate is controlled at 350 sccm to 500 sccm. The vacuum degree is controlled at 1 Pa to 3 Pa during the glow plasma cleaning process, and a negative bias voltage of 350 V to 600 V is set. After the glow plasma cleaning time is over, the gas is exhausted and the vacuum degree is controlled at 3 × 10 -3 ~6×10 -3 Pa.

[0035] Step S2, forming a flat layer on the surface of the graphite substrate. Specifically, the Cr flat layer is prepared by arc coating technology, during which the flow rate of argon gas is controlled to be 50 sccm to 700 sccm, and the vacuum degree is controlled to be 1×10 -1 Pa~3×10 -1 Pa, set the Cr target arc current to 80A-120A, the negative bias voltage to 80V-800V, the duty cycle to 30%-80%, and the deposition time to 2min-30min. Preferably, a two-stage arc coating method is used to form the flat layer, wherein in the first stage, the Cr target arc current is set to 80A-120A, the duty cycle to 30%-80%, and the negative bias voltage to 450V-800V; in the second stage, the Cr target arc current is set to 80A-120A, the duty cycle to 30%-80%, and the negative bias voltage to 80V-450V; and the duration of the first stage is less than the duration of the second stage, for example, the duration of the first stage is 50s-600s, and the duration of the second stage is 100s-1800s.

[0036] Step S3, forming an anti-oxidation layer on the surface of the flat layer. Specifically, the pulsed magnetron sputtering coating technology is switched to prepare the CrN anti-oxidation layer, during which the argon flow rate is controlled to be 50sccm~700sccm, and the high-purity nitrogen with a flow rate of 50sccm~700sccm is set as the reaction gas, the Cr target current is set to 10A~40A, the negative bias voltage is 50V~200V, the duty cycle is 30%~80%, and the deposition time is 20min~180min. Then cool naturally, and when the temperature drops below 70°C, the anti-oxidation layer can be formed. It should be emphasized that the CrN anti-oxidation layer formed by this step is flat and dense, and can be strongly and stably combined with the graphite matrix through the Cr flat layer. At the same time, the CrN anti-oxidation layer has the advantages of low internal stress, small thermal expansion coefficient, high hardness, good thermal stability, toughness, wear resistance, corrosion resistance and oxidation resistance. Thus, the CrN anti-oxidation layer can form a good, stable and long-lasting protection for the graphite matrix.

[0037] The following specific examples are listed to illustrate the graphite composite material and the preparation method thereof provided by the present invention in more detail. It should be noted that the following examples are only used to illustrate the present invention in detail and do not limit the protection scope of the invention in any way.

[0038] Embodiment 1

[0039] This embodiment provides a method for preparing a graphite composite material. Specifically, the preparation method comprises the following steps:

[0040] 1) Pre-cleaning

[0041] Wipe the surface of the graphite substrate to be coated with alcohol to clean the graphite substrate;

[0042] 2) Place the sample

[0043] The graphite substrate cleaned with alcohol is clamped on the hanging rod of the circular rotating frame in the magnetron multi-arc ion sputtering coating equipment, and then the hatch is closed. The hanging rod is rotated while the circular rotating frame is in orbital motion to ensure the uniformity of the film after heating and subsequent sputtering deposition, wherein the rotation frequency of the circular rotating frame is 30Hz.

[0044] 3) Glow Cleaning

[0045] The temperature in the furnace was set at 250°C for 1 h, and the vacuum degree reached 6×10 -3 Pa, the furnace temperature was adjusted to 200 °C, the graphite substrate was glow plasma cleaned for 20 min, the flow rate of high-purity argon as sputtering gas was 500 sccm, the vacuum degree was maintained at 2 Pa, and the negative bias voltage was set to 500 V. After the glow plasma cleaning time was over, the gas was exhausted and the vacuum degree was re-evacuated to 6 × 10 -3 Pa.

[0046] 4) Preparation of Cr flat layer

[0047] The Cr flat layer was prepared by arc coating technology. The furnace temperature was kept at 170°C, the argon flow rate was 400 sccm, and the vacuum degree was 2×10 -1 pa, set the Cr target arc current to 100A, the negative bias voltage to 450V, the duty cycle to 50%, and the deposition time to 68s, then set the negative bias voltage to 150V, the duty cycle to 60%, and deposit for another 600s.

[0048] 5) Preparation of CrN anti-oxidation layer

[0049] The pulsed magnetron sputtering coating technology was switched to prepare the CrN anti-oxidation layer. During this period, the argon flow rate was controlled to 450sccm, the high-purity nitrogen flow rate was set to 200sccm as the reaction gas, the Cr target current was set to 30A, the negative bias voltage was 80V, the duty cycle was 50%, and the deposition time was 2400s.

[0050] 6) Let it cool down

[0051] After the coating is completed, the furnace is cooled naturally. When the temperature drops below 70°C, the graphite composite material sample is taken out and left to stand for at least 24 hours to obtain the desired graphite composite material A. The flat layer thickness of the graphite composite material A is 130nm, the anti-oxidation layer thickness is 1270nm, and the total coating thickness is 1400nm. In the anti-oxidation layer of the graphite composite material A, the atomic percentages of Cr and N are 76% and 24% respectively.

[0052] In order to further illustrate the anti-shedding performance of the anti-oxidation layer of the graphite composite material A, we conducted an anti-shedding performance test on the graphite composite material A. Specifically, after the graphite composite material A was subjected to 638 rapid hot and cold shock cycle tests, the graphite composite material was wiped with a white cloth, and it was found that the anti-oxidation layer on the surface of the graphite composite material did not fall off.

[0053] It should be noted that the conditions for the rapid thermal shock cycle test are: in a normal pressure high-temperature furnace filled with nitrogen, the temperature is increased from room temperature to 700°C and then lowered to room temperature for one temperature change, and one temperature change takes 50 minutes.

[0054] Embodiment 2

[0055] This embodiment provides a method for preparing a graphite composite material. Specifically, the preparation method comprises the following steps:

[0056] 1) Pre-cleaning

[0057] Wipe the surface of the graphite substrate to be coated with alcohol to clean the graphite substrate;

[0058] 2) Place the sample

[0059] The graphite substrate cleaned with alcohol is clamped on the hanging rod of the circular rotating frame in the magnetron multi-arc ion sputtering coating equipment, and then the hatch is closed. The hanging rod is rotated while the circular rotating frame is in orbital motion to ensure the uniformity of the film after heating and subsequent sputtering deposition, wherein the rotation frequency of the circular rotating frame is 30Hz.

[0060] 3) Glow Cleaning

[0061] The temperature in the furnace was set at 250°C for 1 h, and the vacuum degree reached 6×10 -3Pa, the furnace temperature was adjusted to 200 °C, the graphite substrate was glow plasma cleaned for 20 min, the flow rate of high-purity argon as sputtering gas was 500 sccm, the vacuum degree was maintained at 2 Pa, and the negative bias voltage was set to 500 V. After the glow plasma cleaning time was over, the gas was exhausted and the vacuum degree was re-evacuated to 6 × 10 -3 Pa.

[0062] 4) Preparation of Cr flat layer

[0063] The Cr flat layer was prepared by arc discharge sputtering pulse magnetron deposition. The furnace temperature was kept at 170 °C, the argon flow rate was 400 sccm, and the vacuum degree was 2×10 -1 pa, set the pure Cr target arc current to 110A, the negative bias voltage to 450V, the duty cycle to 50%, and the deposition time to 68s, then set the negative bias voltage to 150V, the duty cycle to 60%, and then deposit for another 300s.

[0064] 5) Preparation of CrN anti-oxidation layer

[0065] The CrN anti-oxidation layer was prepared by switching to glow discharge sputtering pulse magnetron deposition. During this period, the argon flow rate was controlled to 450sccm, the high-purity nitrogen flow rate was set to 200sccm as the reaction gas, the purity Cr target current was set to 25A, the negative bias voltage was 60V, the duty cycle was 50%, and the deposition time was 1800s.

[0066] 6) Let it cool down

[0067] After the coating is completed, the furnace is cooled naturally. When the temperature drops below 70°C, the graphite composite material sample is taken out and left to stand for at least 24 hours to obtain the desired graphite composite material B. The flat layer thickness of the graphite composite material B is 70nm, the anti-oxidation layer thickness is 963nm, and the total coating thickness is 1033nm. In the anti-oxidation layer of the graphite composite material B, the atomic percentages of Cr and N are 70% and 30% respectively.

[0068] In order to further illustrate the anti-shedding performance of the anti-oxidation layer of the graphite composite material B, we conducted an anti-shedding performance test on the graphite composite material B. Specifically, after the graphite composite material B was subjected to 644 rapid hot and cold shock cycle tests, the graphite composite material was wiped with a white cloth, and it was found that the anti-oxidation layer on the surface of the graphite composite material did not fall off.

[0069] It should be noted that the conditions for the rapid thermal shock cycle test are: in a normal pressure high-temperature furnace filled with nitrogen, the temperature is increased from room temperature to 700°C and then lowered to room temperature for one temperature change, and one temperature change takes 50 minutes.

[0070] The embodiments of the invention are described above in conjunction with the accompanying drawings, but the invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the inspiration of the invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the invention and the claims, all of which are within the protection of the invention.

Claims

1. A method for preparing a graphite composite material, characterized in that: The graphite composite material comprises a graphite substrate, a flat layer attached to the surface of the graphite substrate, and an anti-oxidation layer attached to the surface of the flat layer; The flat layer is formed of metal Cr, and the anti-oxidation layer is formed of a metal compound CrN; The preparation method comprises the following steps: Step S1, cleaning the graphite substrate; Step S2, forming a flat layer on the surface of the graphite substrate; Step S3, forming an anti-oxidation layer on the surface of the flat layer; In the step S2, a two-stage arc coating method is used to form the flat layer on the surface of the graphite substrate; wherein, in the first stage, the Cr target arc current is set to 80A~120A, the duty cycle is 30%~80%, and the negative bias voltage is 450V~800V; in the second stage, the Cr target arc current is set to 80A~120A, the duty cycle is 30%~80%, and the negative bias voltage is 80V~150V; The duration of the first stage is less than the duration of the second stage; In the step S3, the pulsed magnetron sputtering coating technology is switched to prepare the CrN anti-oxidation layer, the argon flow rate is controlled to 50 sccm ~ 700 sccm, nitrogen is set as the reaction gas, the Cr target current is set to 10A ~ 40A, the negative bias voltage is 50V ~ 200V, the duty cycle is 30% ~ 80%, and the deposition time is 20min ~ 120min.

2. The method for preparing the graphite composite material according to claim 1, characterized in that: The step S1 comprises: Step S11, pre-cleaning: wiping the surface of the graphite substrate to be coated with alcohol; Step S12, placing the sample: clamping the graphite substrate after alcohol cleaning on the hanging rod of the circular rotating frame in the magnetron multi-arc ion sputtering coating equipment, setting the hanging rod to rotate while the circular rotating frame revolves as a whole; Step S13, glow cleaning: at a temperature of 170°C to 400°C and a vacuum degree of 3×10 -3 ~6×10 -3 The graphite substrate was glow plasma cleaned under the condition of Pa.

3. The method for preparing the graphite composite material according to claim 1, characterized in that: In the step S3, the flow rate of nitrogen gas as a reaction gas is 50 sccm to 700 sccm.

4. The method for preparing the graphite composite material according to claim 1, characterized in that: The thickness of the planar layer is between 50nm and 900nm.

5. The method for preparing the graphite composite material according to claim 1, characterized in that: The thickness of the anti-oxidation layer is between 700nm and 8000nm.

6. The method for preparing the graphite composite material according to claim 1, characterized in that: In the anti-oxidation layer, the atomic percentages of Cr and N are 50-80% and 20-50%, respectively.

Citation Information

Patent Citations

  • Composite coating for improving surface performance of carbon-based electrode, graphite electrode and preparation method

    CN115404452A

  • Superalloy article having corrosion resistant coating thereon

    US20050255329A1